Investigation of Current Leakage Mechanisms on InAs Nanoisland Diodes for Radiation Hardness - Hasbullah, Nurul Fadzlin; Ahmad Fauzi, Dhiyauddin (2014)
This research project presents the effects of thermal neutron radiation of fluences ranging from 3 to 9×1013 neutron/cm2 on the electrical behaviour of quantum dot-in-a-well semiconductor samples. The samples are characterized via forward-bias and reverse-bias current densities measurement, capacitance-voltage measurement and temperature dependence measurement. After neutron irradiation of up to 9×1013 neutron/cm2, the leakage current increases both in forward bias and reverse bias by an order of magnitude and two orders of magnitude respectively. Increments are expected to be due to the induced displacement damage effect. Based on ideal diode equation fitting, the ideality factor and series resistance are some of the values that increase with the increasing neutron fluence, indicating a change in the current transport mechanism as well as the doping profile. From the capacitance-voltage measurement, the capacitance is calculated to reduce by up to 6.42%, which is believed to be due to the carrier removal effect. Reduction in the doping densities of the p-region and i¬-region and increment in the doping densities of the n-region on the other hand suggests an effect of Neutron Transmutation Doping. An insight on the reverse-bias leakage current mechanism reveals that the increase in current densities is due to trap-assisted generation-recombination and Frenkel-Poole effect.